New insight into the association between bile infection and clinically relevant pancreatic fistula in patients undergoing pancreatoduodenectomy. (2nd July 2020) - Nakamura, Kota; Sho, Masayuki; Kinoshita, Shoichi; Akahori, Takahiro; Nagai, Minako; Nakagawa, Kenji; Takagi, Tadataka; Ikeda, Naoya
Abstract: Background: The association between bacterial infection and clinically relevant postoperative pancreatic fistula (CR‐POPF) after pancreatoduodenectomy (PD) has not been fully elucidated. Methods: Microbiological data for intraoperative bile culture (BC) and drain culture on postoperative day 4 (DC) were collected. The study population was classified into the following three groups: P1 (positive BC and DC), P2 (positive BC and negative DC), and N (negative BC). A total of 209 patients (P1: 38, P2: 72, and N: 99) who underwent PD between May 2013 and May 2018 met the inclusion criteria of the study. Results: The rate of CR‐POPF was significantly higher in the P1 group (34.2%) than in the P2 (12.5%; P = .007) and N groups (14.1%; P = .008). Between P1 and P2 groups, a significant difference was observed in the proportion of Enterococcus faecalis grown in BC (42.1% vs 4.2%; P < .001). Multivariable logistic regression analysis showed that the presence of E faecalis in bile was independently associated with CR‐POPF. Conclusions: The detection of both bile and postoperative abdominal fluid infections can be more accurate in predicting CR‐POPF. Furthermore, the presence of E faecalis in bile may serve as a novel surrogate marker for CR‐POPF. Abstract : Nakamura and colleagues showed that the detection of both bile infection and postoperative abdominal fluid infection may more accurately predict the development of clinically relevant postoperative pancreatic fistula after pancreatoduodenectomy. The presence of Enterococcus faecalis in bile may serve as a novel surrogate marker for clinically relevant postoperative pancreatic fistula.